A New Best Approximation Result in (S) Convex Metric Spaces. (16th March 2020) - Sabiri, M.; Mouline, J.; Bassou, A.; Sabar, T.
Abstract : Consider a self-mapping T defined on the union of p subsets of a metric space, and T is said to be p cyclic if T A i ⊆ A i + 1 for i = 1, …, p with A p + 1 = A 1 . In this article, we introduce the notion of S convex structure, and we acquire a best proximity point for p cyclic contraction in S convex metric spaces.